Bacówka i hala jako miejsce edukacji zawodowej i kulturowej na Podhalu - Haratyk, Anna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The article presents the specificity of shepherd’s profession, depicts historic ways of training for shepherding, taking into account subsequent stages of practical vocational education. The place of education and work of the Tatra 40shepherds is also characterized. Changes taking place nowadays in both preparation for the profession and in working conditions is also investigated. The impact of these changes and the elimination of shepherding on the natural environment of the Tatra Mountains is emphasized. The article mentions the role of introduction of so-called ‘cultural grazing’ in the Tatra National Park, which is supposed to preserve dying pastoral traditions and make them known to the general public visiting the Tatras for touristic purposes. Head shepherds who undertook cultural grazing try to refer to the old customs and pastoral traditions, and the shepherd’s huts once again becames a home for shepherds and a place of production of dairy products from milk obtained during grazing. Unfortunately, due to the lack of shepherds willing to work in primitive comfort-deprived conditions, the traditional professional structure of this group and systematic education of young generations in the hut dwindled.
Keywords: shepherd’s hut; pasture; shepherding; professional education; Podhale; Tatra Mountains